2013
DOI: 10.1124/jpet.113.204180
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Antagonist Reveals a Potential Role of G Protein–Coupled Receptor 55 in Platelet and Endothelial Cell Function

Abstract: The G protein-coupled receptor 55 (GPR55) is a lysophosphatidylinositol (LPI) receptor that is also responsive to certain cannabinoids. Although GPR55 has been implicated in several (patho)physiologic functions, its role remains enigmatic owing mainly to the lack of selective GPR55 antagonists. Here we show that the compound CID16020046 ((4-[4-(3-In yeast cells expressing human GPR55, CID16020046 antagonized agonistinduced receptor activation. In human embryonic kidney (HEK293) cells stably expressing human GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 46 publications
(94 reference statements)
4
80
2
Order By: Relevance
“…ML193 also blocks pro-nociceptive effects of LPI and LPI-evoked depolarisation of neurons from a brain region, the periaqueductal grey [15], reinforcing previous data linking GPR55 to pain perception [16,17]. CID16020046 has been used to understand the role of GPR55 in the cardiovascular system [12,18,19], in atherosclerosis and intestinal inflammation [20][21][22], and in brain [23]. CID16020046 has extended the association of GPR55 to cancer, blocking LPI-evoked angiogenesis in ovarian carcinoma and migration of breast cancer cells [24,25].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…ML193 also blocks pro-nociceptive effects of LPI and LPI-evoked depolarisation of neurons from a brain region, the periaqueductal grey [15], reinforcing previous data linking GPR55 to pain perception [16,17]. CID16020046 has been used to understand the role of GPR55 in the cardiovascular system [12,18,19], in atherosclerosis and intestinal inflammation [20][21][22], and in brain [23]. CID16020046 has extended the association of GPR55 to cancer, blocking LPI-evoked angiogenesis in ovarian carcinoma and migration of breast cancer cells [24,25].…”
Section: Introductionsupporting
confidence: 66%
“…We previously described CID16020046 [12], which is identical to 6 except that the phenyl ring (position C) is replaced with 4-methylphenyl. CID16020046 was independently identified in an antagonist screen utilising U2OS (Human Osteosarcoma) cells stably expressing GFP-tagged β-arrestin and over-expressing hGPR55, measuring agonist-induced β-arrestin translocation by imaging [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has also been reported that Rimonabant is capable of blocking the GPR55 signaling responses induced by other agonist compounds such as JWH015 and AEA, which for instance trigger intracellular Ca 2+ transients (Lauckner et al 2008, WaldeckWeiermair et al 2008. CID-16020046 is a recently synthesized compound that selectively inhibits GPR55 without inducing any effect via CB1 or CB2, in both yeast and HEK293 cells expressing human GPR55 (Kargl et al 2013). In addition, a β2-adrenergic agonist, (R,R′)-40-methoxy-1-naphthylfenoterol (AMF), has been described as a potent GPR55 inhibitor, blocking both O-1602-and AM251-induced GPR55 signaling in cancer cell lines (Paul et al 2014) and reducing the chemoresistance of carcinogenic cells (Singh et al 2016).…”
Section: The Complex Pharmacology Of Gpr55 (Ligands and Interactions mentioning
confidence: 99%